Skeletal Muscle Energetics and Mitochondrial Function Are Impaired Following 10 Days of Bed Rest in Older Adults. (7th January 2020) - Standley, Robert A; Distefano, Giovanna; Trevino, Michelle B; Chen, Emily; Narain, Niven R; Greenwood, Bennett; Kondakci, Gramoz; Tolstikov, Vladimir V; Kiebish, Michael A; Yu, Gongxin; Qi, Feng; Kelly, Daniel P; et al.
Abstract: Background: Older adults exposed to periods of inactivity during hospitalization, illness, or injury lose muscle mass and strength. This, in turn, predisposes poor recovery of physical function upon reambulation and represents a significant health risk for older adults. Bed rest (BR) results in altered skeletal muscle fuel metabolism and loss of oxidative capacity that have recently been linked to the muscle atrophy program. Our primary objective was to explore the effects of BR on mitochondrial energetics in muscle from older adults. A secondary objective was to examine the effect of β-hydroxy-β-methylbuturate (HMB) supplementation on mitochondrial energetics. Methods: We studied 20 older adults before and after a 10-day BR intervention, who consumed a complete oral nutritional supplement (ONS) with HMB (3.0 g/d HMB, n = 11) or without HMB (CON, n = 9). Percutaneous biopsies of the vastus lateralis were obtained to determine mitochondrial respiration and H2 O2 emission in permeabilized muscle fibers along with markers of content. RNA sequencing and lipidomics analyses were also conducted. Results: We found a significant up-regulation of collagen synthesis and down-regulation of ribosome, oxidative metabolism and mitochondrial gene transcripts following BR in the CON group. Alterations to these gene transcripts were significantly blunted in the HMB group. Mitochondrial respiration and markers of content were both reduced and H2 O2 emission was elevated in both groups following BR. Conclusions: In summary, 10 days of BR in older adults causes a significant deterioration in mitochondrial energetics, while transcriptomic profiling revealed that some of these negative effects may be attenuated by an ONS containing HMB.